Clinically Relevant Mechanisms of Lipid Synthesis, Transport, and Storage. (17th July 2015) - Kalish, Brian T.; Fell, Gillian L.; Nandivada, Prathima; Puder, Mark
Abstract : Lipids not only are fundamental nutrients but also serve as basic structural components of cells and as multifunctional signaling molecules. Lipid metabolism pathways underlie basic processes in health and disease and are the targets of novel therapeutics. In this review, we explore the molecular control of lipid synthesis, trafficking, and storage, with a focus on clinically relevant pathways. To illustrate the clinical relevance of molecular lipid regulation, we highlight how these biochemical processes contribute to the pathogenesis of nonalcoholic fatty liver disease, a component of the metabolic syndrome and a paradigmatic example of lipid dysregulation.